2007
DOI: 10.1007/bf02977688
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of psoralen derivatives and their blocking effect of hKv1.5 channel

Abstract: Previously, we found that a furocoumarin derivative, psoralen (7H-furo[3,2-g][1]benzopyran-7-one), blocked a human Kv1.5 potassium channel (hKv1.5) and has a potential antiarrhythmic effect. In the present study, to develop more potent hKv1.5 blockers or antiarrhythmic drugs, we synthesized ten psoralen derivatives and examined their blocking effects on hKv1.5 stably expressed in Ltk cells. Among the newly synthesized psoralen derivatives, three derivatives (Compounds 5, 9 and 10) showed the open channel-block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Kv1.5 is highly expressed in atrial myocytes [21] and loss-of-function Kv1.5 mutations may cause atrial fibrillation [22]. Kv1.5 is thus an attractive target for the treatment of atrial arrhythmias [13,[23][24][25][26][27][28][29][30][31][32]. Kv1.5 is further expressed in several tumor cells and participates in the regulation of adhesion, proliferation and sensitivity to apoptosis [33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Kv1.5 is highly expressed in atrial myocytes [21] and loss-of-function Kv1.5 mutations may cause atrial fibrillation [22]. Kv1.5 is thus an attractive target for the treatment of atrial arrhythmias [13,[23][24][25][26][27][28][29][30][31][32]. Kv1.5 is further expressed in several tumor cells and participates in the regulation of adhesion, proliferation and sensitivity to apoptosis [33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used in the treatment of psoriasis (Scott et al, 1976), cancer (Fossell et al, 1991;Young, 1993) and arthritis (Malawista et al, 1991). Recently, effects of psoralen on ion channels were reported (Vennekamp et al, 2004;Eun et al, 2005;Eun et al, 2007;Pereira et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that decursin acts as an open channel blocker on the hKv1.5 channel. On the basis of all these results, we suggest that decursin blocks hKv1.5 currents not by its known-mechanism, but rather via a direct one-to-one interaction between the drug and the channel in the open state, like as papaverine (Choe et al, 2003), oxypeucedanin (Eun et al, 2005b), psoralen (Eun et al, 2005a;Eun et al, 2007) and torilin (Kwak et al, 2006). The use-dependence of decursin-induced inhibition of the hKv1.5 channel was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Our studies have focused on the development of antiarrhythmic drug, and we previously reported that papaverine (Choe et al, 2003), oxypeucedanin (Eun et al, 2005b), psoralen and their derivatives (Eun at al., 2005a;Eun et al, 2007) and torilin (Kwak et al, 2006) inhibited the hKv1.5 current. The present study was examined to investigate the effect of decursin from A. gigas on hKv1.5 channels using the whole-cell patch-clamp technique.…”
mentioning
confidence: 89%